2006
DOI: 10.1111/j.1365-2958.2005.05038.x
|View full text |Cite
|
Sign up to set email alerts
|

Rad52 depletion in Candida albicans triggers both the DNA‐damage checkpoint and filamentation accompanied by but independent of expression of hypha‐specific genes

Abstract: SummaryWe have analysed the effect of RAD52 deletion in several aspects of the cell biology of Candida albicans . Cultures of rad52 D strains exhibited slow growth and contained abundant cells with a filamentous morphology. Filamentation with polarization of actin patches was accompanied by the induction of the hypha-specific genes (HSG) ECE1 , HWP1 and HGC1 . However, filament formation occurred in the absence of the transcription factors Efg1 and Cph1, even though disruption of EFG1 prevented expression of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 76 publications
(110 reference statements)
7
88
0
1
Order By: Relevance
“…In contrast to the colony and cell morphology phenotypes exhibited by double-strand-break repair mutants (Andaluz et al, 2006;Legrand et al, 2007), including strains derived from the same parental background as used in this study, the mutants grew like wild-type yeast cells in liquid cultures at 30 u C (data not shown). We characterized the growth rates of the deletion mutant strains and observed that the BER and NER mutants had a doubling time similar to that of the parental strain (Table 4).…”
Section: Gene Disruption and Phenotypic Analysismentioning
confidence: 47%
“…In contrast to the colony and cell morphology phenotypes exhibited by double-strand-break repair mutants (Andaluz et al, 2006;Legrand et al, 2007), including strains derived from the same parental background as used in this study, the mutants grew like wild-type yeast cells in liquid cultures at 30 u C (data not shown). We characterized the growth rates of the deletion mutant strains and observed that the BER and NER mutants had a doubling time similar to that of the parental strain (Table 4).…”
Section: Gene Disruption and Phenotypic Analysismentioning
confidence: 47%
“…The ability to switch among these morphologies is required for C. albicans pathogenicity (38,39), suggesting that multiple morphologies contribute to host infection. Filamentous growth can be triggered by various stimuli, including oxidative stress (40), activation of the DNA damage, and replication checkpoints due to exogenous or endogenous DNA damage (41,42), or by cell-cycle delays resulting from perturbed microtubule dynamics or spindle checkpoint activation (43,44; reviewed in ref. 45).…”
Section: Resultsmentioning
confidence: 99%
“…These conditions more-or-less mimic certain host conditions. Interestingly, recent experiments have revealed a seemingly new mechanism for induction of filamentous growth that is caused by the perturbation of cell-cycle progression and is, in at least some cases, independent of the cAMP/PKA and MAP-kinase pathways (Bai et al, 2002;Bachewich et al, 2003;Andaluz et al, 2006; AtirLande et al, 2005;Bensen et al, 2005;Chapa y Lazo et al, 2005). An intriguing observation is that interfering with either an early or a late cell-cycle event, or with events thought to activate distinct cell-cycle checkpoints, appears to have strikingly similar effects on cell morphogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In C. albicans, the spindle-assembly checkpoint was shown to be required for nocodazole-induced filamentous growth (Bai et al, 2002). Recently, Andaluz et al (2006) reported that Rad52p depletion triggers the DNA-damage checkpoint and constitutive filamentation. These observations raise the important question of whether the cell-cycle checkpoints may play active roles in promoting filamentous growth under conditions that perturb cell-cycle progression.…”
mentioning
confidence: 99%